1981
DOI: 10.2527/jas1981.5351204x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Experience on the Learning Ability of Yearling Horses

Abstract: Twenty-four yearling Quarter Horse fillies were divided into three groups (I) very limited handling, (II) intermediate handling and (III) extensive handling. At about 14 months of age, each horse was preconditioned for 2 weeks and then run in a simple place-learning T-maze test in which it had to locate its feed. Thirty trials were run daily for 20 days, with the location of the feed changed each day. To retire from the maze, a horse had to meet the criterion: 11 correct responses in 12 tries, with the last ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The level of fearful reactions develops especially in juvenile life on the basis of interaction between genetic fond and factors of environment (Boissy 1995). It was also found that handling during ontogenesis and before testing accelerates learning (Heird et al 1983). Hart (1985) describes an experiment in which animals were exposed to negative (electric shock) and positive handling.…”
Section: Resultsmentioning
confidence: 99%
“…The level of fearful reactions develops especially in juvenile life on the basis of interaction between genetic fond and factors of environment (Boissy 1995). It was also found that handling during ontogenesis and before testing accelerates learning (Heird et al 1983). Hart (1985) describes an experiment in which animals were exposed to negative (electric shock) and positive handling.…”
Section: Resultsmentioning
confidence: 99%
“…Nervous horses exhibit specific behavioural patterns and higher overall activity index levels, and are typically less trainable than more docile horses (Heird et al 1981;McCann et al 1988). More highly reactive horses may also pose greater risks to humans involved in equestrian activities.…”
Section: Introductionmentioning
confidence: 98%
“…T-maze tasks have been used extensively to investigate various aspects of brain function, including spatial working memory (Zimmerberg, Sukel & Stekler, 1991; Wan, Pang & Olton, 1994; Nagahara & Handa, 1997), long-term reference memory (Olton & Papas, 1979), perseveration (Riley, Lochry, Shapiro & Baldwin, 1979), and foraging strategy such as the use of “win-shift” versus “win-stay” strategies in response to different reinforcement contingencies (Szelest & Cohen, 2006). Much of this work has been done in rodents, but when scaled appropriately, the T-maze can also be suitable for non-rodent species as well, including the ferret (Park & Baum, 1999), cat (Burgess, Villablanca, Levine, 1986), squirrel monkey (Peretti & Baird, 1976), horse (Heird, Lennon & Bell, 1981), goat and sheep (Hosoi, Swift, Rittenhouse & Richards, 1995). …”
Section: Introductionmentioning
confidence: 99%